Pengaruh Kebersyukuran dan Kebermaknaan Hidup Terhadap Kecemasan Masa Depan Mahasiswa - Isna Nur Faizah; Agus Salim; Komarudin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
College students are an educated group of individuals who bring hopes and expectations to be fulfilled as they enter their studies. Thoughts about the future can lead to anxiety. An unclear and uncertain future may cause feelings of helplessness and worry, particularly when someone feels confused and unable to control what lies ahead. This can prevent them from planning effectively and result in persistent anxiety. This study aims to understand how future anxiety is influenced by gratitude and a sense of life purpose. The research method used is quantitative with a non-experimental design. The population of this study consists of college students, with a sample of 168 active students in Yogyakarta selected through cluster random sampling. Data analysis reveals that there is an influence of gratitude and life purpose on future anxiety. The study results were tested using multiple regression analysis with a significance level of 0.000 (p < 0.05). The T-test results for gratitude (X1) show a significance value of 0.017 (p<0.05), and the significance value for the life meaning variable is 0.001 (p<0.05). Therefore, both variables individually influence future anxiety among university students in Yogyakarta.